2020
DOI: 10.1158/1078-0432.ccr-20-1727
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Antiangiogenic Therapy with Cisplatin and Gemcitabine Chemotherapy in Patients with Nasopharyngeal Carcinoma

Abstract: Purpose: Induction cisplatin and gemcitabine chemotherapy is a standard treatment for locally advanced nasopharyngeal carcinoma (NPC). Inhibition of VEGF axis has been shown to promote maturation of microvasculature and improve perfusion. We conducted a four-arm study to assess the effect of two doses of either sunitinib or bevacizumab with chemotherapy in NPC.Patients and Methods: Patients with treatment-na€ ve locally advanced NPC were treated with three cycles of 3-weekly cisplatin and gemcitabine preceded … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…14 Currently, the main molecularly targeted therapeutic drugs with proven efficacy in the treatment of NPC are epidermal growth factor receptor (OMIM: 131550) inhibitors and vascular endothelial growth factor inhibitors. 15,16 Previous studies have demonstrated the clinical efficacy and good safety of molecular targeted therapy in NPC. However, many studies are only in the preclinical or early research stage, 17 and more phase III clinical trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…14 Currently, the main molecularly targeted therapeutic drugs with proven efficacy in the treatment of NPC are epidermal growth factor receptor (OMIM: 131550) inhibitors and vascular endothelial growth factor inhibitors. 15,16 Previous studies have demonstrated the clinical efficacy and good safety of molecular targeted therapy in NPC. However, many studies are only in the preclinical or early research stage, 17 and more phase III clinical trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with chemotherapeutic agents, the use of targeted therapy and immunotherapy in recurrent NPC is relatively limited, and in most cases they are not used alone, but in combination with chemotherapeutic agents or radiotherapy to provide better benefits [ 115 , 116 , 117 , 118 , 119 ]. A clinical study published by Ng et al showed that weekly IMRT with docetaxel plus cetuximab was shown to be effective in advanced recurrent NPC compared to TPF-induced chemotherapy, with a 3-year progression-free survival rate of 35.7% [ 107 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
“…The inhibition of angiogenesis could enhance the effectiveness of standard chemoradiotherapy against NPC. Combination of VEGF inhibitor bevacizumab with chemotherapy promoted microvasculature maturation, enhanced immune infiltration and exhibited promising tumor response ( 172 ). Combination therapy of apatinib with cisplatin showed a synergistic effect in inhibition of tumor growth, repression of VEGFR-2 expression and reduction in microvascular density in preclinical models ( 173 ).…”
Section: Targeting Tumor Microenvironment In Nasopharyngeal Carcinoma...mentioning
confidence: 99%